Penerapan Pendekatan Teaching at the Right Level (TaRL) Untuk Meningkatkan Hasil Belajar Matematika - Savitri, Ni Made Tara; Baidowi; Suntoko, M. Iwan (Mandalika Mathematics and Educations Journal, 2024)
This research is motivated by the low mathematics learning outcomes of students. This research aims to improve mathematics learning outcomes using the Teaching at the Right Level (TaRL) approach with the Problem-Based Learning model. The TaRL approach is a teaching method based on students' ability levels. The main subjects of this research are cube and rectangular prism in cycle 1, prism in cycle 2, and pyramid in cycle 3. The research was conducted from March to May 2024 in class VIII A of SMP Negeri 1 Mataram. The type of research is Classroom Action Research with three cycles. Each cycle consisted of planning, implementation, observation, evaluation, and reflection. The data collection techniques in this research used observation activities and learning outcome tests. The results of this research showed an improvement in mastery learning outcome in each cycle, with mastery learning in Cycle I at 55.882%, Cycle II at 70.588%, and Cycle III at 85.294%. This indicates that the TaRL approach can be used to improve student learning outcomes.